ARAH PROGRAMUNGGULAN PENDIDIKAN KETERAMPILAN KERAJINAN DALAM PERSAINGAN GLOBAL - I Ketut Sunarya (Jurnal Cakrawala Pendidikan, 2001)
Nowadays tIle wlleeL~" oj'tlle Indonesian natioll'S life are turning on tIle lowestruts due to tile continual multidinlensi()nal crisis in politics, .\"ecurily, and economy. Italso injects the products oj'education in the jiJrm (J/hunzan res()urce..'" whose competitivepower is increasingly g()il1g.far below tllat ofatller developing countries.In entering tIle twenty-.(irst century tile universitya..\" tIle center ofexcellence willplaya very i(npOrlant part in tIle preparation 0.[ individuals witll tecllnological and11umanitarian orientati(Jns. A,11(Jng tile fiJrenl()st cllaracteristics related to tllat aspect areorientation to prob/enl solving and quality of'work and care in ~pendingtime, which arepossessed by tile cultural type of tile nlodern man. In answer to tllat cllallenge tileuJliversity i.\' greatly in need ofself-ordering, of being ever readyfor conlpetition, and ofcontinually searching for opportunities to assert its self-e.xistence. And it can assert itsself-existence by presenting prinle progranls tllat are profe..\'sional and ready to supportprocesses ofproduction and possess tIle creativity tllat enables tllemselves to create new.fields qfworkfor J'ob seekers.In times to come there will be increasingly m()re intense c(Jmpetition. The brightfuture of the Ilandicraft arts in meeting tile needs of tourism and also being a primesource oj'tlle national dividend is opening wide so tllat otller institutions are alreadybeginning to present similar relatedprogral11s. Tllis does not eliminate tIle possibility fllatthe Handicraft Skill Course Program of the Faculty of Languages and Arts, StateUniversity of Yogyakarta, will overlook tile opportunity, beco111e a neglected courseprograJl1, andfinally remain only in memory. In relation to tllat, it needs self-ordering.Here are si.x suggested points tllat prime progralns sllould give elnpllasis on: producing(1) Iluman resources able to Ilandle educati()n in /landicrqft arts who possess strongtlleoretical cOl1lpetence, (2) 11uman resources Wll0 conduct researcll on, searcll for, anddiscover Ilandicraji arts to forl1lulate new tlleories witll tlleln able to be resource persons,(3) 11un1an resources ready to he 11andicrafl art critics delivering tl1eir criticisms so tllatpeople know well the meanings within handicraft arts, and (4) human resources able tobe conzpetent Ilarldicrq(t art designers, (5) trail1ing experts in tile field practice ofmaking11andicraft' art products, Wllicll demand\' not only able 11ands but also mastery ofprOdlJction mae/lines, and (6) preparing Iluman resources WllO are ready to becomeIlandicrafl art business people and marketing managers WllO know well about patentrigllts and appreciate and acknowledge otllers ' works so that tllere is no piracy.